Pickwickian Manners and Customs - Fitzgerald, Percy, 1834-1925 (Salt Lake City, UT : Project Gutenberg, 2007)
"Pickwickian Manners and Customs" by Percy Fitzgerald is a historical account written in the late 19th century. The book explores the cultural and social customs surrounding Charles Dickens's "The Pickwick Papers," examining how it has influenced English society. It highlights how the narrative and its characters, notably Mr. Pickwick and his friends, reflect a bygone era filled with humor and distinct societal behaviors. The opening of "Pickwickian Manners and Customs" provides an insightful context for the enduring appeal of "The Pickwick Papers." Fitzgerald notes its profound impact on readers and critics alike, emphasizing the meticulous detail that has gone into its analysis over the decades. Historical references are made to various manners, fashions, and customs from the time of Pickwick that have since faded away, underscoring the novel's role as an entertaining yet serious examination of social norms. The text reflects on significant transformations in society, highlighting how the whimsical journeys of Mr. Pickwick continue to resonate, functioning as both a charming narrative and a historical document of the Victorian period. (This is an automatically generated summary.)
Release date is 2007-06-25
Transcribed from the [1897] Roxburghe Press edition by David Price
Keywords: Dickens, Charles, 1812-1870. Pickwick papers